Functional Results of Transverse Extended Incision in Cervical Neck Dissection - Chiesa-Estomba,Carlos Miguel (2021)
Abstract Introduction Multiple incisions have been described for the surgical approach of cervical neck nodes. All of these descriptions are associated with better or worse exposure of the surgical field as well as with different functional and aesthetic results, which are not always satisfactory. Objective Compare the transverse cervical incision with the classic incision in J or U. Methods This is a retrospective study of 47 patients who required cervical neck dissection between June 15, 2016 and June 15, 2017.A transversal incision was made in these surgeries, and their results were then compared with those of a group of 57 patients treated between January 1, 2010 and January 1, 2012, in whose cases an incision in J or U was made. Results Regarding the incision type, complications were present in 4 (8.5 %) cases in the transversal incision group, and in 7 (12.2 %) patients of the group of traditional incisions in J or U, without statistical differences (p = 0.078). The only variables associated with complications of healing in the two groups was body mass index (BMI) < 18.5. The patients showed subjective satisfaction with the aesthetic result of the transverse incision, with an average of 7.51 vs 6.20 in the J or U incision. Conclusion The transverse incision represents a safe, aesthetic, and oncologically adequate option, associated with a lower cicatricial retraction rate, without significant complication rate and allowing adequate exposure of the surgical field, similar to the obtained with the classic incision in J or U.